Implementing an interpreter for a functional language; Parallel virtual machine versus remote procedure calls : performance comparison; Adherence of capsules to the mammalian oesophagus / [mikrofilem] - Hazinah Kutty Mammi 403599; Samura Ali 222938; Kamalrulnizam Abu Bakar 562895; Syed Anuar Faua'ad Syed Muhammad 450962 (Essex : University of Essex, 1998)
Thesis (Msc in Computer Science) - University of Essex, 1998